Genitourinary radiology cases - Sanyal, Rupan ([New York] : Oxford University Press, 2015)
This volume features 129 cases that cover the spectrum of benign and malignant genitourinary conditions and imaging modalities for a practical, easy-to-use review guide.
Previously issued in print: 2014.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on May 23, 2016).
Keywords: Genitourinary organs -- Radiography -- Case studies; Diagnostic imaging -- Case studies